Treatment of Highly Polluted Industrial Wastewater Utilizing Clean and Low Cost Technologies: Review Article - Abdelfattah, Ibrahim (Journal of Environmental Accounting and Management, 2026)
A comprehensive review article dealing with clean and low cost technologies for treatment of highly polluted industrial wastewater will be detailed. These technologies covering: the biological processes including anaerobic methods with high production of biogas and lower production of sludge, aerobic methods will be excluded due to the higher sludge production and the added cost of aeration. Biosorption and adsorption processes including different clays and plant wastes will be included due to economic reasons and sustainability factors. Furthermore, advanced oxidation processes (AOPs) which are utilized in case of the higher ranges of toxic effluents as a cost effective technologies will be discussed. Solar processes which utilize the nature UV-source will be also involved. The review article is supported with case studies for relieving the noxious effects of wastewaters before discharging it into the surrounding environment. A valuable recommendations are presented to finalizing the review article drawing the best planning to get rid of the hazardous effects of the industrial effluents.